2018
DOI: 10.4314/gmj.v52i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic tympanic membrane perforations: characteristics and factors affecting outcome

Abstract: Not indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 27 publications
2
27
0
16
Order By: Relevance
“…Majority of patients (72, 63.2%) presented to ENT clinic within a week time and single perforation was the commonest observation (107, 93%), which simulates to study of Sogebi, where patients presented to clinic between few hours to 23 days with mean duration after injury was 3 days. 16 Similarly, Wani from India carried out study in 2016 on traumatic TM perforation and he also observed that 323 (92.3%) patients had single perforation while 27 (7.7%) had multiple perforations. 17 In current study conductive hearing loss was more common (94, 82.5%), however mild degree of hearing impairment was recorded in 59 patients (51.8%).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Majority of patients (72, 63.2%) presented to ENT clinic within a week time and single perforation was the commonest observation (107, 93%), which simulates to study of Sogebi, where patients presented to clinic between few hours to 23 days with mean duration after injury was 3 days. 16 Similarly, Wani from India carried out study in 2016 on traumatic TM perforation and he also observed that 323 (92.3%) patients had single perforation while 27 (7.7%) had multiple perforations. 17 In current study conductive hearing loss was more common (94, 82.5%), however mild degree of hearing impairment was recorded in 59 patients (51.8%).…”
Section: Discussionmentioning
confidence: 95%
“…17 According to available literature spontaneous healing of TTMP occurs in 80 -100% cases. 5,[10][11][12][13][14][15][16]18,19 As slap on the ear was more common resulting perforation at anterio-inferior quadrant of TM on left side hence there was statistically significant association between cause of trauma and site and side of perforation (x=24.13, p=0.020), (x=57.10. p=0.000), that is supported by study of Sannigrahi who found significant association between mode of injury and tympanic membrane perforation after three months (χ2 = 23.30; p = .00001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the patients with ear trauma had physical non-explosive ear trauma sometimes associated with single episodes of vertigo. [28] Vertigo is a common symptom in patients who sustained trauma to the head and neck region that resulted from motor vehicle accidents, falls, assaults, and contact sports. [29] Sometimes, the trauma was minor head traumas which occurred a fairly long time before the onset of vertigo.…”
Section: Discussionmentioning
confidence: 99%